Effect of storage temperature, water activity, oxygen headspace concentration and pasteurization intensity on the time to growth of Aspergillus fischerianus (teleomorph Neosartorya fischeri). (June 2020) - dos Santos, Juliana Lane Paixão; Samapundo, Simbarashe; Djunaidi, Stefani; Vermeulen, An; Sant'Ana, Anderson S.; Van Impe, Jan; Devlieghere, Frank
Abstract: This study aims to assess, by means of a full factorial design, the effect of storage temperature (10–30 °C), water activity ( a w, 0.87–0.89), headspace oxygen (O2 ) level (0.15–0.80%) and pasteurization intensity (95 °C–105 °C/15sec) on the time to visible growth (tv, days) of Aspergillus fischerianus on acidified Potato Dextrose Agar (aPDA, pH 3.6) for up to 90 days. Moreover, in order to validate the results obtained on aPDA, 12 conditions were selected and assessed in concentrate strawberry-puree based medium. Overall, storage temperature had the greatest effect on the tv of A. fischerianus on the evaluated conditions. At 10 °C, no visible growth was observed over the 90 day incubation period, whilst visible mycelia (diameter ≥ 2 mm) were present in 37% and 89% of the conditions at 22 °C and 30 °C, respectively. Pasteurization intensity had only a minor effect on the outgrowth of A. fischerianus . Growth inhibition was observed when a w was reduced to 0.870 ± 0.005 in combination with very low headspace O2 levels (0.15% ± 0.10) in both, aPDA and concentrate strawberry-based media, regardless of the incubation temperature and heat pasteurization intensity. Overall, longer tv 's were required when incubation was done at 22 °C compared to 30 °C. Ultimately, the effect of O2 (0.05 and 1%) and pasteurization intensity (95 °C and 105 °C/15sec) were evaluated on totally 22 fruit purees (un-concentrates and concentrates) over a 60 day storage period. None of the concentrates purees ( a w ≤0.860) evaluated in this study supported the growth of A. fischerianus. On the other hand, A. fischerianus growth inhibition was only observed when the O2 levels were ≤0.05% on un-concentrates fruit purees ( a w  ≥ 0.980) stored at ambient temperature (22 °C). Combination of multiple stress factors effectively inhibited growth of A. fischerianus . In general, storage of fruit purees at low temperatures (<10 °C) or distribution in the form of concentrates can be considered as important strategies to prevent the growth of spoilage associated heat-resistant moulds. Highlights: Temperature (10–30 °C) had the greatest effect on A. fischerianus time to visible growth. Small a w differences resulted in A. fischerianus growth, delay or inhibition. The combination of low O2 (0.15%) and a w (0.87) resulted in A. fischerianus inhibition. A. fischerianus growth inhibition was observed at O2  ≤ 0.05% for high a w purees. Fruit compounds promote inhibition or delay of A. fischerianus visible growth.